2012
DOI: 10.1364/oe.20.004067
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon-enhanced terahertz emission from a hemicyanine self-assembled monolayer

Abstract: Abstract:Emission of terahertz radiation is observed when surface plasmons are excited on a thin film of gold, in the Kretschmann geometry. When a hemicyanine-terminated alkanethiol self-assembled monolayer of thickness 1.2 nm is deposited on the gold film, stronger terahertz emission is observed. Our experimental results confirm that enhanced terahertz emission is possible from planar gold surfaces when surface plasmons are excited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…As Ramakrishnan et al recently pointed out [18], the different observed dependencies of the THz fluence on pump power do not necessarily contradict * Corresponding author: dmitry.polyushkin@tuwien.ac.at each other, rather they may be associated with different regimes of THz emission that occur under these different experimental conditions. Experiments for which OR is invoked typically involve relatively low peak-power Ti:sapphire laser pulses (see Refs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…As Ramakrishnan et al recently pointed out [18], the different observed dependencies of the THz fluence on pump power do not necessarily contradict * Corresponding author: dmitry.polyushkin@tuwien.ac.at each other, rather they may be associated with different regimes of THz emission that occur under these different experimental conditions. Experiments for which OR is invoked typically involve relatively low peak-power Ti:sapphire laser pulses (see Refs.…”
Section: Introductionmentioning
confidence: 86%
“…Since then different metallic materials and structures have been used to generate THz radiation: nanostructured silver and gold films [11][12][13], semicontinuous metal films [14,15], and metallic nanoparticles [15,16]. Two distinct mechanisms have been proposed to explain the observed generation of THz radiation: OR on metal surfaces [10,14,[16][17][18] and multiphoton photoelectron emission (MPE) [11,15,19,20]. In the latter case, the THz radiation is produced by the ponderomotive acceleration of the ejected electrons caused by the high electric field gradients that occur in the proximity of metal surfaces [21], owing to plasmonic enhancement [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ramakrishnan and Planken have reported THz emission from a thin percolated gold film of 10 nm thickness, having localized surface plasmon (LSP) hot spots [5]. Recently Ramakrishnan et al observed THz emission from ordered NLO chromophores in a molecular monolayer at the surface plasmon resonance condition [6]. In these studies, the THz emission amplitude is quadratic in the excitation field, suggesting that the THz emission is based on the second-order NLO process.…”
mentioning
confidence: 99%
“…Light reflected at the sample was detected by the spectrometer using another bundle optical fiber (0.4 mm in diameter). The THz emission was measured using the optical geometry, described in previous papers [5,6]. As the light source, a Ti:sapphire oscillator (Scientific XL, Femtolasers) was used, generating pulses of 50 fs duration, at a central wavelength of 800 nm at a repetition rate of 11 MHz.…”
mentioning
confidence: 99%
“…In recent years, terahertz related research and technology development has acquired a significant interest of the scientific community all around the globe. This is because of the various applications that terahertz radiations can advance [1][2][3][4][5].This include high speed communication [6], sub wavelength imaging [7], slow light devices [8], bio sensing [9], spectroscopy etc. The development of the waveguides at terahertz frequencies has been one of the primary focus of research in this fast growing area of science and technology.…”
Section: Introductionmentioning
confidence: 99%